Stabilization and Structural Change in Russia, 1992-94 - Koen, Vincent (IMF Working Papers; Working Paper ;, 1995)
Macroeconomic stabilization and structural reforms in Russia since 1992 have been proceeding in a rather chaotic fashion. The Russian variety of economic gradualism has seen a sharp decline in output, though less than indicated by official statistics, and relatively resilient household consumption. Hyperinflation has been avoided so far by tightened financial policies, but remains a threat. Conventional macroeconomic wisdom on the relation between money, prices and output is relevant for Russia. Moreover, stabilization and structural change interact and are mutually reinforcing.